Sales technology and salespeople’s ambidexterity: An ecosystem approach - Giovannetti, Maria; Cardinali, Silvio; Sharma, Piyush (Emerald, 2020)
Purpose – This paper aims to explore the impact of salespeople’s goal orientation and self-regulatory mode on their performance through sales ambidexterity and sales technology infusion (STI) using a sales technology ecosystem approach.